Class I and II histone deacetylase expression is not altered in human amyotrophic lateral sclerosis: Neuropathological and positron emission tomography molecular neuroimaging evidence. Issue 4 (16th July 2019) - Dios, Amanda M.; Babu, Suma; Granucci, Eric J.; Mueller, Kaly A.; Mills, Alexandra N.; Alshikho, Mohamad J.; Zürcher, Nicole R.; Cernasov, Paul; Gilbert, Tonya M.; Glass, Jonathan D.; Berry, James D.; Atassi, Nazem; et al.
Abstract: Introduction: There is an unmet need for mechanism‐based biomarkers and effective disease modifying treatments in amyotrophic lateral sclerosis (ALS). Previous findings have provided evidence that histone deacetylases (HDAC) are altered in ALS, providing a rationale for testing HDAC inhibitors as a therapeutic option. Methods: We measured class I and II HDAC protein and transcript levels together with acetylation levels of downstream substrates by using Western blotting in postmortem tissue of ALS and controls. [ 11 C]Martinostat, a novel HDAC positron emission tomography ligand, was also used to assess in vivo brain HDAC alterations in patients with ALS and healthy controls (HC). Results: There was no significant difference in HDAC levels between patients with ALS and controls as measured by Western blotting and reverse‐transcription quantitative polymerase chain reaction. Similarly, no differences were detected in [ 11 C]Martinostat–positron emission tomography uptake in ALS participants compared with HCs. Discussion: These findings provide evidence that alterations in HDAC isoforms are not a dominant pathological feature at the bulk tissue level in ALS.